Chapter «A' quai Lucan seguitava». Su Boccaccio lettore della Pharsalia - Gensini, Niccolò (Studi e saggi, 2020)
Lucan was one of the most widely read and studied classical authors during the Middle Ages, a reference point for teaching, historiography and literature. The essay attempts to outline Giovanni Boccaccio's profile as a reader of Pharsalia in the different ages of his literary production and in his critical judgment, placing him in the context of fourteenth-century reception. The different ways of reading Lucan's masterpiece, from the almost literal imitation of some scenes in the Filocolo, to the punctual references to situations, images and characters in the works of maturity, testifies the inexhaustible attention of Boccaccio towards the poet of «plus quam civilia bella».